The Trinity in history : a theology of the divine missions. - Doran, Robert M., 1939- (Lonergan studies., 2012)
"The Trinity in History is the first volume in a new series by Robert M. Doran that uses the thought of Bernard Lonergan to develop a unified field structure for systematic work in theology. Building on his successful and thought-provoking Theology and the Dialectics of History and What Is Systematic Theology?, Doran works out a starting point for a contemporary theology of history and proposes a new application of the 'psychological analogy' for understanding the Christian doctrine of the Trinity.